Late and Multiple Bidding in Competing Second Price - Marta Stryszowska (Fondazione Eni Enrico Mattei (FEEM), 2004)
Internet auctions, such as those on eBay, are known for multiple bidding and sniping. Buyers send bids in the closing seconds of an auction, knowing that bids arriving after the closure of the auction are not counted. They also bid several times at the same auction. We model Internet auction as a dynamic multi-unit auction. This let us explain the rationality of both sniping and multiple bidding. By submitting multiple bids, buyers co-ordinate between auctions, so that all objects are finally sold and no-one has to pay too high a price. When bidders submit multiple bids, they might bid very late in the end.
Keywords: D44; 330; Auctions; Electronic Commerce; Internet; Auktion; Internet; E-Business; Auktionstheorie